2017
DOI: 10.1021/acssuschemeng.7b01462
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions of Isolated Bio-Oil Compounds and Their Effect on Bitumen Interfaces

Abstract: Bio-oils derived from low-value or waste biomass have been shown to be useful as low-cost, sustainable additives to improve the adhesion or moisture resistance of bituminous asphalt binder. The chemical profile of bio-oil is complex, and identifying the most active compounds in the mixture and understanding how they work to modify bitumen properties is essential for synthesizing bio-based additives with desired characteristics and performance. Hexadecanamide and hexadecanoic acid, two surfactants prevalent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 63 publications
2
28
0
1
Order By: Relevance
“…We previously used AFM–IR to study the chemical composition of modified bitumen and its interface with mineral fillers or glass, showing how some compounds preferentially accumulate at the bitumen–mineral interface. Xing et al performed AFM–IR on thermally aged samples of bitumen and styrene-butadiene-styrene-modified bitumen and showed that there are some differences in chemical composition of the surface of the bitumen and the bulk. , A recent study used AFM–IR to identify changes in bitumen surface morphology and composition with decreasing temperatures . Here, we used AFM–IR to examine the surface composition of spin-coated bitumen thin films with or without UV aging.…”
Section: Introductionmentioning
confidence: 99%
“…We previously used AFM–IR to study the chemical composition of modified bitumen and its interface with mineral fillers or glass, showing how some compounds preferentially accumulate at the bitumen–mineral interface. Xing et al performed AFM–IR on thermally aged samples of bitumen and styrene-butadiene-styrene-modified bitumen and showed that there are some differences in chemical composition of the surface of the bitumen and the bulk. , A recent study used AFM–IR to identify changes in bitumen surface morphology and composition with decreasing temperatures . Here, we used AFM–IR to examine the surface composition of spin-coated bitumen thin films with or without UV aging.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has shown that certain chemical compounds in bitumen tend to migrate toward and separate out at bitumen interfaces. For example, fatty acid compounds can accumulate at the bitumen–silica interface and increase the susceptibility of asphalt concrete to moisture damage. We also showed that saturated wax crystallizes as lamellae at the bitumen–air surface that wrinkles under compressive strain to produce the characteristic “bee-like” structures often observed on bitumen surfaces. , …”
Section: Introductionmentioning
confidence: 67%
“…However, many acid groups are probably hydrated, which would shift their SO and S–O absorption peaks to ranges similar to those of ionic groups ( 3d , 6c , or 7c ). Carboxylic acid compounds have previously been implicated in reducing the moisture-stripping resistance of bitumen in asphalt pavement. Sulfoxides were found to be less susceptible to water displacement from aggregate surfaces than carboxylic acids but more susceptible than nitrogen compounds . Sulfuric and sulfonic acids are more easily ionizable than carboxylic acids and merit further observation in case they have a similarly damaging effect.…”
Section: Resultsmentioning
confidence: 99%